Understanding an organizational change and development intervention applied in a Global Software Industry: A case study: A Case Study - Lima, Rayfran; Albuquerque, Luis; Ayres, Marcelo; Silva, Suelen; Oran, Ana; França, César (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
CONTEXT: Organizational changes and development interventions are being used as adaptive mechanisms for answering to the market and internal demands to remain flexible, and adaptable without losing productivity and quality. However, applying appropriate transitions involving team restructuring and project reorganization is still a challenge for most software industry companies. OBJECTIVE: This study aims to carry out a case study to identify the motivations and actions that supported an episodic organizational change (EOC) in a software industry company that end up in an adoption of a new model of team structure and project organization, called Model B. In addition, we intend to identify the main impacts and lessons learned perceived by the stakeholders during the transition process and the use of Model B for 2 years. RESULTS: The 5 identified motivations for this EOC were answered by an intervention composed of 3 main actions. The efficacy of the intervention was evaluated by comparing the motivations and achieved results. In addition, we present the dynamic of the definition and implementation of Model B, as well as new improvements applied over the 2 years of its use. The lessons learned are composed of 3 factors that can boost and 8 factors that can hinder the transition from the prior model to Model B, followed by some extra suggestions to improve the company’s EOC process. CONCLUSION: Our findings show evidence that not adopting change management knowledge can make implementing EOC in the software industry more challenging and prone to inefficiency or failure. On the other hand, applying risk management considering known critical factors can help in generating a plan that is more efficient and able to take advantage of critical success factors and avoid or mitigate the disadvantages arising from critical failure factors.